2021
DOI: 10.1021/acs.jpcc.1c04464
|View full text |Cite
|
Sign up to set email alerts
|

Multicapacitor Approach to Interfacial Proton-Coupled Electron Transfer Thermodynamics at Constant Potential

Abstract: Theoretical calculations of interfacial thermodynamics at constant potential enhance understanding of heterogeneous electrocatalytic reactions. Herein, a strategy is devised for computing reaction thermodynamics for electrochemical proton-coupled electron transfer (PCET), a key elementary step in a wide range of electrocatalytic processes. In this approach, Gibbs free energies obtained from constant charge periodic density functional theory calculations are transformed to grand potentials by using a grid-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…This result was consistent with earlier work, which demonstrated that constant-charge PCET reaction energetics are uniquely defined as a function of the effective surface charge . The computational analysis of the graphite-conjugated organic acids showed that the internal energy U [ q graph ( E )] can be calculated using the DFT energy U DFT and a shift associated with the capacitive contributions of the constantly charged surface adsorbate: …”
Section: Thermodynamics Of Electrochemical Pcetsupporting
confidence: 90%
See 1 more Smart Citation
“…This result was consistent with earlier work, which demonstrated that constant-charge PCET reaction energetics are uniquely defined as a function of the effective surface charge . The computational analysis of the graphite-conjugated organic acids showed that the internal energy U [ q graph ( E )] can be calculated using the DFT energy U DFT and a shift associated with the capacitive contributions of the constantly charged surface adsorbate: …”
Section: Thermodynamics Of Electrochemical Pcetsupporting
confidence: 90%
“…A computational analysis of PCET reactions at the surface of graphite-conjugated organic acids showed that the energetics of interfaces containing adsorbates with constant charge are determined by the graphite electrode surface charge, q graph . In this case, the Taylor series expansion for an interface that is polarized by both counter-charges in the EDL, denoted q , and constantly charged adsorbates, q ads , simplifies to a function of q graph only (Figure A–B): where E 0 is the graphite electrode potential of zero free charge (PZFC).…”
Section: Thermodynamics Of Electrochemical Pcetmentioning
confidence: 99%
“…Note that this method, combined with the extrapolation procedure in Equation 4, provides a direct way to determine potential dependent electrochemical barriers by using just the outputs of a DFT calculation along with the transition state structures, without the need for any a priori assumptions to its value. 16,22…”
Section: Moving Atoms By Small Displacementsmentioning
confidence: 99%
“…11,12,14 In the past decade, a variety of methods to address this challenge have been developed. 11,12,[14][15][16][17][18][19][20][21][22][23][24][25] These methods can be broadly grouped into two categories, extrapolation and grand-canonical schemes. Extrapolation methods seek to determine activation energies at the limit of infinite cell size by correcting DFT energies for finite cell size effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation